Effects of silver nanoparticles on the physiology, stress, and mineral uptake of banana cultivars in vitro and greenhouse - Mendoza, Natalia; Hidalgo, Karen; Troya, Lorena; Sánchez-Timm, Eduardo; Vielma, Joel; Vanegas, María Eulalia; Bogdanchikova, Nina; Pestryakov, Alexey; Chong, Pablo (Frontiers in Plant Science, 2025)
IntroductionThis study explores the effects of silver nanoparticles (AgNPs) from the formulation Argovit™ on physiological stress responses and mineral uptake in banana cultivars, both in vitro and under greenhouse conditions. These specific AgNPs have been previously studied for their antifungal activity against Fusarium oxysporum, highlighting their potential as a disease control agent in banana cultivation. Evaluating their phytotoxicity is crucial to determine safe application levels, particularly at the concentrations previously shown to be effective.MethodsThe primary objective is to expose the phytotoxic effects, nutrient uptake, and translocation mechanisms of AgNPs based on their application method, either foliar or drench.Results and discussionIn vitro experiments on the Cavendish banana var. Williams, with shoots cultured in media supplemented with AgNPs at concentrations of 0, 25, 50, 100, and 1000 mg L-1, showed significant reductions in shoot formation, length, chlorophyll content, and leaf number as AgNP concentrations increased. Rooting experiments revealed similar trends with high AgNP concentrations resulting in a decreasing root number and size. Greenhouse experiments on Gros Michel bananas, evaluating AgNP uptake through foliar and drench applications at 0, 25, 50, and 100 mg L-1, monitored over a month, showed no statistically significant differences in growth parameters between treated plants and controls. However, tissue analysis revealed higher leaf Ag concentrations than roots and stems. The study also analyzed antioxidant gene expression via qPCR, targeting genes such as MaSOD (superoxide dismutase), MaCAT (catalase), MaAPX (ascorbate peroxidase), and MaGPX (glutathione peroxidase), showing altered profiles in response to AgNP exposure and indicating induced oxidative stress. This research underscores the complex interactions between AgNPs and banana plants, emphasizing the need for further study to optimize safe and effective AgNP application in agriculture, balancing crop protection and environmental safety.